(untitled) (Research, Society and Development, 2022)
The number of people affected by the catabolic disease diabetes mellitus (DM) grows worldwide, which demands the development of new therapeutic and monitoring technologies to assist in the treatment and reduce the chances of complications arising from the decompensation of the clinical picture. Thus, the objective was to carry out a literature review seeking the effects of innovations in improving treatment and quality of life for diabetics. For this, an integrative bibliographic review of literature of a qualitative nature was carried out, in the SciELO, LILACS and PubMed databases, with the descriptors in health sciences (DeCS) associated with the boolean operator AND, as follows: “Diabetes Mellitus AND Inovações”, “Diabetes Mellitus AND Tecnologia”, “Diabetes Mellitus AND Continuous Glucose Monitoring”, “Diabetes Mellitus AND Infusion Pump”, “Diabetes Mellitus AND Artificial Pancreas”. After analyzing 13 articles, it was identified that flash glucose monitoring (FGM), carbohydrate counting, artificial pancreas, MiniMed 670G, iLet Bionic Pancreas and continuous infusion system for insulin are the main components by technological categories indicated for glycemic control and quality of life of people with type 1 diabetes mellitus, however, most health professionals and patients affected by DM are unaware of these therapeutic innovations. It is concluded that it is necessary to promote more health education activities among the interdisciplinary health team and the general population, regarding care and reduction of metabolic decompensation among diabetics.